GEGURITAN KEDIS: ANALISIS SEMIOTIK - Sri Trisna Dewi, Ayu (Humanis, 2015)
This study discusses Geguritan Kedis with structur and semiotic studies. Used structural theory is a structural theory Teeuw and used semiotic is a semiotic theory of Charles Sanders Peirce. To simplify the anaslysis method used consists of several syage items, namely: (1) stage providing data by using the method of reading and techniques used are the recording techniques, and assisted with translation techniques. (2) stage of data analysis, using qualitative methods and techniques used are descriptive analytic techniques, and (3) stage of data analysis using formal methods informally assisted with inductive deductive thinking patterns. Conclusion from this analysis is structur shape comprising: (1) code language and literature, experince variations in suara gatra, wilangan kecap, and suara pamatut, (2) used is the language style of comparison, and style parable, (3) variety of language used is bahasa bali alus and bahasa bali kasar. Narrative structure include: Tempest theme of love, characters are the main charaters and secondary characters, straight flow path used, and there is background setting, time, and atmosphere. Semiotic analysis in Geguritan Kedis covers the iconic elements of the icons of the time, indexical about physical appearance, and symbolic of the character names.
Keywords: structur, iconic, indexical, symbolic